The Pragmatic Analysis on Ganjar’s Speech in Mata Najwa ‘3 Bacapres Bicara Gagasan’ - Dwi Santoso (Attractive : Innovative Education Journal, 2024)
The inaugural meeting of the potential presidential candidates of the Republic of Indonesia took place at the 3 Bacapres Bicara Gagasan ‘3 Presidential Candidates Talking Ideas’ event on September 19, 2023, organized by Mata Najwa at Gadjah Mada University. This forum is very important as it requires every potential presidential candidates for the Republic of Indonesia to effectively communicate the entirety of their speech. This research tries to specifically describe the various ways in which the principle of cooperation is violated and the resulting effects on discussion in Ganjar Pranowo's speech. The research utilizes speech data from the presidential candidate of the Republic of Indonesia, obtained from Najwa Shihab's YouTube channel. The data were examined using qualitative descriptive methods, employing a pragmatic theoretical approach, specifically focusing on the notion of cooperative principles and implicatures. Transcription was used to acquire research data. The findings are Ganjar Pranowo tends to violate the maxim of quantity, maxim of relevance and maxim of quality. The purpose of violating the maxim is to inform, avoid, and refuse/rebut.